Essentials in Minimally Invasive Gynecology Manual Skills Construct Validation Trial. Issue 1 (July 2020) - Munro, Malcolm G.; Advincula, Arnold P.; Banks, Erika H.; Auguste, Tamika C.; Chahine, E. Britton; Grace Chen, Chi Chiung; Curlin, Howard L.; Jorgensen, Elisa M.; Kim, Jin Hee; King, Cara R.; Lucas, Joelle; Milad, Magdy P.; et al.
Abstract : OBJECTIVE: To establish validity evidence for the Essentials in Minimally Invasive Gynecology laparoscopic and hysteroscopic simulation systems. METHODS: A prospective cohort study was IRB approved and conducted at 15 sites in the United States and Canada. The four participant cohorts based on training status were: 1) novice (postgraduate year [PGY]-1) residents, 2) mid-level (PGY-3) residents, 3) proficient (American Board of Obstetrics and Gynecology [ABOG]–certified specialists without subspecialty training); and 4) expert (ABOG-certified obstetrician–gynecologists who had completed a 2-year fellowship in minimally invasive gynecologic surgery). Qualified participants were oriented to both systems, followed by testing with five laparoscopic exercises (L-1, sleeve-peg transfer; L-2, pattern cut; L-3, extracorporeal tie; L-4, intracorporeal tie; L-5, running suture) and two hysteroscopic exercises (H-1, targeting; H-2, polyp removal). Measured outcomes included accuracy and exercise times, including incompletion rates. RESULTS: Of 227 participants, 77 were novice, 70 were mid-level, 33 were proficient, and 47 were experts. Exercise times, in seconds (±SD), for novice compared with mid-level participants for the seven exercises were as follows, and all were significant ( P <.05): L-1, 256 (±59) vs 187 (±45); L-2, 274 (±38) vs 232 (±55); L-3, 344 (±101) vs 284 (±107); L-4, 481 (±126) vs 376 (±141); L-5, 494 (±106) vs 420 (±100); H-1, 176 (±56) vs 141 (±48); and H-2, 200 (±96) vs 150 (±37). Incompletion rates were highest in the novice cohort and lowest in the expert group. Exercise errors were significantly less and accuracy was greater in the expert group compared with all other groups. CONCLUSION: Validity evidence was established for the Essentials in Minimally Invasive Gynecology laparoscopic and hysteroscopic simulation systems by distinguishing PGY-1 from PGY-3 trainees and proficient from expert gynecologic surgeons. Abstract : Structured laparoscopic and hysteroscopic manual skills testing distinguished novice from mid-level residents, and board-certified obstetrician–gynecologists from fellowship-trained minimally invasive gynecologic surgeons.